Larvicidal Evaluation against Aedes aegypti and Antioxidant and Cytotoxic Potential of the Essential Oil of Tridax procumbens L. Leaves - Lethicia B. Brandão; Lizandra L. Santos; Rosany L. Martins; Alex B. L. Rodrigues; Erica de M. Rabelo; Allan K. R. Galardo; Sheylla S. M. da S. de Almeida (The Scientific World Journal)
The present study evaluated the antioxidant, cytotoxic, and larvicidal potential of the essential oil of Tridax procumbens leaves, as well as identified the compounds present in the essential oil. The antioxidant activity was evaluated by the sequestration method of 2,2-diphenyl-1-picrylhydrazyl radical, the cytotoxic activity was evaluated using Artemia salina, the larvicidal bioassay was performed with larvae in the third stage of development of the Aedes aegypti mosquito, and the identification of the metabolites was performed by gas chromatography coupled to the mass spectrometer (GC-MS). The phytochemical oil analysis showed the presence of 20 compounds, with thymol and γ-terpinene being the main ones. It presented antioxidant activity with an IC50 of 194.51 μg mL−1, demonstrating antioxidant activity in the highest concentrations tested. It presented low cytotoxic activity against A. salina, with an LC50 of 1238.67 μg mL−1, demonstrating atoxicity in the concentrations tested. The essential oil presented good larvicidal activity when compared to the literature, with an LC50 = 79.0 μg mL−1 in 24 hours and LC50 of 69.15 μg mL−1 in 48 hours. In this way, it was possible to identify that the essential oil of the leaves of T. procumbens presented potential for the development of a natural larvicide, as well as antioxidant activity satisfactory to the radical DPPH and low toxicity to A. salina.